ELECTRICAL CONDUCTIVITY OF MAGNETIC EMULSIONS WITH CHAIN MICROSTRUCTURE IN MAGNETIC FIELD - A. R. Zakinyan; A. A. Zakinyan (Наука. Инновации. Технологии, 2022)
Introduction: The paper experimentally investigates the properties of emulsions whose dispersion medium is represented by a magnetic fuid, and the dispersed phase is formed by water. Such media are new functional materials whose properties are not fully understood at the present time. Structure formation in these media can lead to signifcant changes in their macroscopic properties. In particular, the study of the electrophysical properties of magnetic emulsions is relevant. Experimental studies and their results: It is shown that under the infuence of a magnetic feld in the emulsion, chain aggregates are formed from droplets of the dispersed phase. This change in the microstructure of the emulsion affects its macroscopic properties. The specifc electrical conductivity of emulsions was measured. It was shown that under the infuence of relatively weak external magnetic felds (~ 1 kA/m), the electrophysical parameters of the emulsion can change several times. The dependence of the specifc electrical conductivity of emulsions on the magnitude and direction of the external magnetic feld, as well as on the concentration of the emulsion, was studied. Analysis of the results obtained: The detected peculiarities of electrical conductivity of the emulsion are interpreted on the basis of available theoretical data. In particular, a comparison was made with the results of calculations within the framework of the effective medium approximation. The qualitative agreement of the obtained experimental data with the existing models is shown. Conclusion: Based on the conducted research, it is concluded that the electrical conductivity of the synthesized and studied magnetic emulsions signifcantly depends on the infuence of the magnetic feld. This indicates the possibility of their practical application as magnetically controlled media.